Emergence of uncommon KL38-OCL6-ST220 carbapenem-resistant Acinetobacter pittii strain, co-producing chromosomal NDM-1 and OXA-820 carbapenemases - Tian, Chongmei; Xing, Mengyu; Fu, Liping; Zhao, Yaping; Fan, Xueyu; Wang, Siwei (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives: To characterise one KL38-OCL6-ST220 carbapenem resistant Acinetobacter pittii strain, co-producing chromosomal NDM-1 and OXA-820 carbapenemases. Methods: A. pittii TCM strain was isolated from bloodstream infection (BSI). Antimicrobial susceptibility tests were conducted via disc diffusion and broth microdilution methods. Stability experiments of blaNDM-1 and blaOXA-820 carbapenemases genes were further performed. Whole-genome sequencing (WGS) was performed on the Illumina and Oxford Nanopore platforms. Multilocus sequence typing (MLST) was analyzed based on the Pasteur and Oxford schemes. Resistance genes, virulence factors and ISs were identified with ABRicate based on ResFinder 4.0, virulence factor database (VFDB) and ISfinder. Capsular polysaccharide (KL), lipoolygosaccharide (OCL) and plasmid reconstruction were tested using Kaptive and PLACNETw. PHASTER was used for prediction of prophage regions. A comparative genomics analysis of all ST220 A. pittii strains from the public database was further carried out. Point mutations, average nucleotide identity (ANI), DNA-DNA hybridization (DDH) distances and pan-genome analysis were further performed. Results: A. pittii TCM was ST220Pas and ST1818Oxf with KL38 and OCL6, respectively. It was resistant to imipenem, meropenem and ciprofloxacin but still susceptible to amikacin, colistin and tigecycline. WGS revealed that A. pittii TCM contained one circular chromosome and four plasmids. Tn125 composite transposon including blaNDM-1 was located in the chromosome with 3-bp target site duplications (TSD). blaOXA-820 carbapenemase gene and many virulence factors were also identified. The stability assays revealed blaNDM-1 and blaOXA-820 were stable by passage in antibiotic-free medium. Moreover, twelve prophage regions were identified in the chromosome. Phylogenetic analysis showed there are 11 ST220 A. pittii strains, and one collected from Anhui, China was closely related. All ST220 A. pittii strains presented high ANI and DDH values, ranged 99.85%-100% for ANI and 97.4%-99.9% for DDH. Pan-genome analysis revealed 3,200 core genes, 0 soft core gene, 1,571 shell genes and 933 cloud genes among 11 ST220 A. pittii strains. Conclusions: The co-existence of chromosomal NDM-1 and OXA-820 carbapenemases in A. pittii presents a huge challenge for healthcare setting, increased surveillance of this species in hospital and community settings is urgently needed.